2005
DOI: 10.1530/rep.1.00850
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of pre- and peri-implantation in vitro cultured, somatic cell nuclear transfer and in vivo derived ovine embryos

Abstract: The processes of cellular differentiation were studied in somatic cell nuclear transfer (SCNT), in vitro cultured (IVC) and in vivo developed (in vivo) ovine embryos on days 7, 9, 11, 13, 17 and 19. SCNT embryos were constructed from in vitro matured oocytes and granulosa cells, and IVC embryos were produced by in vitro culture of in vivo fertilized zygotes. Most SCNT and IVC embryos were transferred to recipients on day 6 while some remained in culture for day 7 processing. In vivo embryos were collected as z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Some of these features correspond to those previously reported in studies examining only one of the two developmental processes, either elongation or gastrulation [17], [18], [19], [20], [22], [39], [40], [41]. Here, however, we describe for the first time a high incidence of E/EE uncoupling, a result which emerged from our concomitant analysis of the two processes.…”
Section: Discussionsupporting
confidence: 90%
“…Some of these features correspond to those previously reported in studies examining only one of the two developmental processes, either elongation or gastrulation [17], [18], [19], [20], [22], [39], [40], [41]. Here, however, we describe for the first time a high incidence of E/EE uncoupling, a result which emerged from our concomitant analysis of the two processes.…”
Section: Discussionsupporting
confidence: 90%
“…As this phenomenon was equally common in spherical/ovoid embryos and the more advanced filamentous embryos, it seems as if embryonic growth, at least for a period, is not disturbed by the lack of an epiblast. Similar findings have been reported for ovine SCNT embryos (Tveden-Nyborg et al 2005). It may be speculated that hypoblast formation is a dominant process, which, if the inner cell mass is low in cell number, consumes all cells of the inner cell mass.…”
Section: Discussionsupporting
confidence: 87%
“…In sheep, it has been documented that serum-enriched embryo culture and SCNT procedures cause a retardation of embryo development and cell differentiation on D7-19 of gestation (Tveden-Nyborg et al 2005). In addition, Bertolini et al (2002) found that on D16 of gestation, the length of bovine IVP embryos was shorter than embryos produced in vivo and, moreover, they displayed ED deviations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cattle, vimentin protein expression has been detected in the epiblast of in vivo embryos in the case of other ungulates, including pigs (day 9) (Prelle et al. 2001) and sheep (day 11) (Tveden‐Nyborg et al. 2005).…”
Section: Discussionmentioning
confidence: 99%